MAGIC AND ITS LAWS: MAGICAL PRACTICES IN THE COUNTRYSIDE IN ROMAN ANTIQUITY IN THE LIGHT OF AN AGRONOMIC TREATY OF THE V CENTURY A.D. - Schmidt Totti, Luis Augusto [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2022)
This article is about chapter 35, book I, of the agronomic treatise Opus agricultura (Palladius -5th century AD), in which the author presents some prescriptions for the protection of farm against pests and climatic phenomena. It analyzes magical practices identified according to the so-called laws of magic, which define every magical act based on the principles of contiguity, similarity, and contrariety. These three formulations are synthesized in the ideas that the elements in contact are or remain united, that the equal produces the equal, and that the contrary acts on the contrary. From this it is possible to perceive the interpenetration of the principles in question and their interaction with other elements of magical-religious symbology.
Keywords: agriculture; ancient Rome; magic; magical thinking